Innovative stabilization of the lumbar spine. Fast track from surgery to removal of all restrictions in professional athletes - Dmitry N. Dzukaev; Andrey V. Zholinsky; Anton V. Borzenkov; Anton I. Toporskiy (Спортивная медицина: наука и практика)
Purpose of the study: To date, there is a lack of data on the effectiveness and safety of surgical treatment of Th10–L2-segment fractures of the spine in patients who can be classified as professional athletes. The most frequently used methods of surgical intervention do not allow a full-fledged return to the pre-injury level of physical activity.Materials and methods: In the described clinical case, an 18-year-old professional cyclist (height 180 cm, weight 68 kg) sustained a spinal injury during a fall from a bicycle at an international cycling competition. Immediately after the injury, he was admitted to hospital where he was diagnosed with a closed burst fracture of the first lumbar vertebral body with neurological complications and a large bony fragment causing stenosis of the spinal canal (B2N3 AO Spine). He underwent primary stabilisation surgery 10 days after the injury. However, two months after the operation, the athlete continued to have severe radicular pain syndrome in the right leg (6 points on the visual analogue scale (VAS)), right-sided monoparesis of the thigh and lower leg muscles (up to 3 points on the MRCS scale), hypoesthesia on the anterolateral surface of the right leg, and a significant decrease in quality of life (54% on the Oswestry questionnaire).Taking into account the persisting symptoms, the patient underwent two-stage surgical treatment: extended rigid stabilisation at the first stage, and short semi-rigid stabilisation using PEEK rods at the second stage (5 months later) after the first signs of fusion.Results: Already after the first stage of treatment there was a complete regression of pain syndrome (0 points on VAS), regression of right-sided monoparesis, significant improvement according to the Oswestry questionnaire (2%). Four months later, the second stage of surgical treatment was performed, which made it possible to maintain reliable stabilisation in the transition zone between the thoracic and lumbar spine, including dynamic loads on the fixed segment. As a result, the athlete was able to return to active training without the risk of destabilisation of the system, and at follow-up for 10 months after the second stage of surgery, the athlete did not experience any limitations in performing sport-specific loading of any intensity.Conclusion: The proposed method of two-stage surgical treatment allowed a professional cyclist to return to the pre-injury level of physical activity six months after the second stage of surgical treatment of a complicated spinal injury. This clinical case demonstrates the effectiveness of PEEK rods in delayed fixation and active rehabilitation without restrictions.